Potential economic feasibility of suweg flour production as a high carbohydrate food ingredient - Permadi, Adi; Wulandari, Annisa Desna (Universitas Ahmad Dahlan, 2023)
Tubers are high-carbohydrate food ingredients that are widely available in Indonesia. However, not all tubers in Indonesia are used and developed optimally. Suweg is a tuber plant that can grow in yards or fields without special maintenance. Some farmers in Java, Sumatra, and Eastern Indonesia already know Suweg. Suweg is a very potential source of food. Suweg has prospects to be developed into tuber flour and starch. Suweg, which belongs to the taro tribe, is being looked at by several groups in the food and health supplement industry as a raw material because of its nutritional content. In this study, tubers of suweg were processed into intermediate products in the form of suweg flour using a modified salt solution immersion method and fermentation using a lactic acid bakery starter (BAL). The resulting suweg flour is brownish-white powder, clean from other impurities, with a distinctive suweg odor and a slightly characteristic suweg taste and passes through an 80-mesh sieve. The economic simulation results in producing 85.8 kg of suweg flour for 1 month packaged in 1 kg obtained a base price of Rp. 4,290,000, R/C ratio of 1.3, BEP volume of 39.55 packages, BEP price of Rp. 1,977,660. Keywords: tubers, suweg flour, intermediate products, lactic acid bacteria